The Effectiveness of Case Method to Students’ Paraphrasing Write Skills - Emawati, Emawati; Noermanzah, Noermanzah (IJLECR (International Journal of Language Education and Cultural Review), 2023)
Paraphrasing writing skills are useful for students in writing scientific papers, especially in providing an explanation of a concept using different language from the reference we quote without changing the meaning so as to avoid plagiarism. Writing paraphrases requires critical thinking skills and creativity in processing sentences without changing the meaning. In fact, there are still many students who are not skilled in writing paraphrases. One way to improve students’ paraphrasing writing skills is to apply the case method. For this reason, this study aims to determine how much influence the case method has on students’ paraphrasing abilities. This research used experimental method with pre-experimental designs. The research design used the One Groups Pretest-Posttest Design. Data collection using paraphrase writing test technique. Analysis of research data by: assessing the results of each student’s paraphrasing writing, calculating data normality tests, and conducting hypothesis testing with the Paired Sample T Test using SPSS 23. The results showed that there was a significant effect of the case method on the paraphrasing ability of students of the Management Study Program, Faculty of Economics, Universitas PGRI Palembang. The influence is indicated by the Sig value. (2-tailed) of 0.01 is smaller than 0.05. Students are able to paraphrase using their own language in several techniques, namely changing active sentences to passive ones, shortening sentences, changing sentences to become longer, and replacing words with words that have the same meaning. It’s just that there are still some students who paraphrase by only changing some of the words in the quoted sentence by writing the equivalent of the word.